Nearpod-Based Interactive Learning Media in Improving Learning Outcomes of Class V Elementary School Students - Yosefh Daniel Marcelino Banjarnahor; Daitin Tarigan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is motivated by a learning process that rarely uses learning media in delivering material, so that students are less interested in following learning so that it affects student learning outcomes. The purpose of this study is to determine the richness, practicality, and effectiveness of using nearpod-based learning media. The type of research used is development research (Research and Development) which uses the ADDIE development model with 5 stages of research, namely Analyze, Design, Development, Implementation, and Evaluation. The subject of this study was a grade V student of SDN 101775 Sampali. The instruments used in data collection are teacher interviews, material and media validation questionnaires, education practitioner questionnaires, and tests. The results of the development of nearpod-based learning media on fractional material, showed that the results of material validation got a percentage of 93.75% with the category